Effects of extended postmortem aging on selected beef muscles intended for retail sale - Karney, Erin D., author; Woerner, Dale R., advisor; Belk, Keith E., committee member; Tatum, J. Daryl, committee member; Pendell, Dustin L., committee member (Colorado State University. Libraries, 2014)
In order to mimic beef commonly found in retail supermarkets, paired strip loins (NAMP #180) and top sirloin butts (NAMP #184) were obtained from USDA Choice carcasses with a marbling score ranging from Small00 to Small50 (n = 15) and USDA Select carcasses with a marbling score ranging from Slight50 to Slight99 (n = 15) at a commercial packing plant. Samples were collected from 3 separate groups of carcasses in order to replicate each aging and display period three times. At 48 hours postmortem, paired strip loins and top sirloin butts were portioned into 3-inch sections, vacuum-sealed, and stored 14, 21, 28, 35, 49, or 63 days postmortem. For both strip loin and sirloin sections, once the aging period was designated, the sections were stored in a vacuum-sealed bag at 0°C (± 1°C) and in the dark until their assigned aging period was complete. Two steaks from each aged section for each muscle was placed in a styrofoam tray with a polyvinyl chloride overwrap and placed in a multi-deck retail display case equipped with LED lighting (Hussmann Model No. M3X8GEP) and set at 2°C for 72 hrs. A third steak cut from each aged section was immediately cooked, and Warner-Bratzler shear force (WBSF) analysis was measured to determine the effects of the aging period on tenderness without the display period. During the display period, each steak was evaluated every 8 hours by a minimum of 8 trained panelists for lean color, external fat color, lean percent discoloration, and L* a* b* color values. A trained sensory panel for tenderness and flavor attributes, including off-flavors, also was used to evaluate steaks. As steaks were subjected to longer periods of postmortem aging, WBSF values decreased and trained sensory panel tenderness ratings improved. A 72 h display time reduced (P < 0.05) WBSF values of strip loin and sirloin steaks. A minimum of 28 d of postmortem aging was required to improve the WBSF values of low Choice and Select strip loin steaks compared with the same strip loins steaks aged for 14 d, and a minimum of 35 d of postmortem aging was required to improve sensory tenderness ratings for low Choice and Select strip loin steaks. Strip loin steaks aged up to 28 d before retail display had little impact on display life and the incidence of off-flavors; however, there was no tenderness advantage over 14 d aged steaks from low Choice and Select strip loins. Thirty-five days of postmortem aging were required to achieve an improvement in WBSF compared to that achieved with 14 d aging for low Choice and Select top sirloin steaks, and trained sensory panel scores indicated that at least 49 d of postmortem aging was required to improve the myofibrillar tenderness of low Choice and Select sirloin steaks. Sirloin steaks aged 35 d and beyond produced undesirable lean color scores in as early as the first 24 h of retail display, and top sirloin steaks aged only 14 d and displayed an additional 72 h had relatively intense levels of oxidized and sour/acidic flavors present. Top sirloins cannot be aged for enough time to improve tenderness and maintain a considerable level of display life, and extended aging time is not a viable option for top sirloins intended for retail display and sale.
Keywords: aging; beef; color; sirloin; strip loin; tenderness